2010
DOI: 10.1007/s11664-010-1189-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Usage of Thermoelectric Generators on Ships

Abstract: The useful waste heat potential for a bulk carrier has been evaluated as a preliminary step towards developing a thermoelectric generator (TEG) waste heat recovery system for ships. A medium-sized bulk carrier produces 6.2 MW of waste heat, and the most promising usable sources for the TEG are shown herein to be the exhausts from the main engine and the sludge oil incinerator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…However, for small ships and other waste heat sources, Thermoelectric Generators (TEGs) represents a promising solution direction. N.R Kristiansen et al [11] analyzed the waste heat sources on a median size bulker ship equipping a main engine of 7.8 MW Conceptual Design and Performance Analysis of an Exhaust Gas Waste Heat Recovery System for a 10000TEU Container Ship and found that incinerators were most promising application for TEGs. Moreover, important factors for successful TEGs applications were commercialization of materials research and reduced price/Watt power output TEGs can bring [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, for small ships and other waste heat sources, Thermoelectric Generators (TEGs) represents a promising solution direction. N.R Kristiansen et al [11] analyzed the waste heat sources on a median size bulker ship equipping a main engine of 7.8 MW Conceptual Design and Performance Analysis of an Exhaust Gas Waste Heat Recovery System for a 10000TEU Container Ship and found that incinerators were most promising application for TEGs. Moreover, important factors for successful TEGs applications were commercialization of materials research and reduced price/Watt power output TEGs can bring [12].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a preliminary study regarding the application of TEG in on-ship incinerators in which potential benefits were conceptually estimated, 3) more technical examinations on the realistic combination of TEG and marine power plants have not been reported. Since many advanced thermoelectric materials and cascaded devices are becoming available for high temperature range, a pilot study of the applicability of thermoelectric generation to the boiler section of marine steam turbines (among a great many other options), in particular the first application possibility mentioned above, is presented in this paper through the CFD modeling approach.…”
Section: Introductionmentioning
confidence: 99%
“…Board incinerators are used for burning the onboard waste instead to be thrown overboard to pollute the sea water. The incinerators are the most favourable TEG systems due to the availability of their high-temperature differences [101,102].…”
Section: Marine Applicationsmentioning
confidence: 99%